Chemical Reactor Design - Peter Harriott (New York CRC Press, 2021)
Featuring case studies and worked examples that illustrate key concepts in the text, this book contains guidelines for scaleup of laboratory and pilot plant results, methods to derive the correct reaction order, activation energy, or kinetic model from laboratory tests, and theories, correlations, and practical examples for 2- and 3-phase reaction systems, including bubble columns, slurry reactions, trickle-led reactors, and fluidized beds. A comprehensive reference, the book offers strategies to analyze and interpret kinetic data for homogeneous and heterogeneous reactions, practical design procedures, rate equations, and analytical models for improved reactor performance.
Keywords: Chemical Engineering